A public health study on the participation mechanism of social capital in the governance of public sports space in dilapidated urban communities – a case study of Changsha City, Hunan Province - Xinze, Li; Xiaoyi, Zhang; Qiao, He (Frontiers in Public Health, 2023)
In China, managing public sports facilities in dilapidated urban communities is a significant livelihood initiative and crucial to raising inhabitants' quality of life. An empirical study on the participation mechanism of social capital in the governance of public sports space in dilapidated communities was carried out using questionnaires, quantitative statistics, and logical deduction. The research subjects were dilapidated communities in Changsha, Hunan Province. According to the study, both individual and collective social capital positively influence the governance of public sports facilities in dilapidated urban communities; personal social capital also positively affects the availability of public sports facilities in dilapidated communities through social interaction; collective social capital positively influences the availability of public sports facilities in dilapidated urban communities through social trust, and Collective social capital positively impacts all of the above. Based on this, it is possible to actively cultivate social capital to enhance the administration of public sporting venues in dilapidated urban communities in the future.